2020
DOI: 10.1088/1742-6596/1554/1/012065
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Student Errors in Solving Ordinary Differential Equations Based on SOLO Taxonomy

Abstract: This study aims to describe the errors of student in solving ordinary differential equation (ODE) problems based on SOLO taxonomy. In this case there are 5 kinds of errors, namely concept errors, using data, language interpretation, technical, and making conclusions. This descriptive study involved 10 ODE research subjects. The research results obtained are the subjects of research tends to make mistakes in the five SOLO taxonomy errors. The reason is because students are not skilled in using formulas, are not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
2
1
0
Order By: Relevance
“…The previous finding is consistent with prior studies (Bray, 2013;Ingram et al, 2015;Willingham et al, 2018Yarman et al, 2020, which emphasized that mathematical error-analysis contributes to providing students with opportunities to show interest in the learning topic, respect and accept students' opinions, speak in a correct language, develop useful questions, in addition to giving students an opportunity to express their thoughts, and criticize them along with others' thoughts.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The previous finding is consistent with prior studies (Bray, 2013;Ingram et al, 2015;Willingham et al, 2018Yarman et al, 2020, which emphasized that mathematical error-analysis contributes to providing students with opportunities to show interest in the learning topic, respect and accept students' opinions, speak in a correct language, develop useful questions, in addition to giving students an opportunity to express their thoughts, and criticize them along with others' thoughts.…”
Section: Discussionsupporting
confidence: 89%
“…Also, it is due to the benefits of the learning environment supported by mathematical error-analysis activities in increasing classroom interaction and participation, and helping students reduce their anxiety of making errors in the classroom as well as overcoming some challenges that face them, through reducing embarrassment, reducing mathematical errors and encouraging students to keep on learning mathematics. This result was reported by previous studies (Ayuwanti & Dwisiswoyo, 2021;Brodie, 2008;Heinze, 2005;Ingram et al, 2015;Kent, 2017;Kyaruzi et al, 2020;MCcarthy et al, 2016;Palkki & Hästö, 2019;Qadri, 2012;Rach et al, 2012;Rushton, 2018;Willingham et al, 2018;Yarman et al, 2020), which indicated that mathematical error-analysis enhances students' interaction and effective discussion, develops analytical skills, corrects misunderstandings and misconceptions and leads to creating a strong learning educational environment in the classroom, as it increases classroom interaction between teacher and students and among students themselves.…”
Section: Discussionsupporting
confidence: 80%
“…Kastolan stage is one of the tools to analyze the description answer errors students make in solving questions. Kastolan's stages consist of conceptual, procedural, and technical errors (D et al, 2021;Najwa, 2021;Yarman et al, 2020). The mistakes made by the students can be information and reference on the progress and shortcomings to be made in the ethnomathematical learning process.…”
Section: Introductionmentioning
confidence: 99%